Concept mapping toward competency: Teaching and assessing undergraduate evidence‐informed practice. Issue 2 (17th March 2021) - Lafave, Lynne M. Z.; Yeo, Michelle; Lafave, Mark R.
Abstract: Background: Undergraduate students in healthcare professions need to develop critical thinking skills in order to be prepared to deliver patient‐centered high‐quality care upon graduation. The new Canadian Athletic Therapy Association (CATA) competency framework includes a "scholar" role, placing emphasis on knowledge and skills related to evidence‐informed practices (EIP). Educators are expected to develop their student's EIP skills; however, little is known about the optimal educational approaches to accomplish this task. The study objective was to examine concept mapping as a teaching and learning strategy to deepen the understanding of EIP and examine the validity and reliability of a concept mapping scoring rubric. Method: A concept mapping approach to teaching EIP was piloted in an upper‐level research methods and statistics course. Students ( N = 15) participated in a pretest post‐test concurrent nested mixed‐method intervention study that analyzed the impact of concept mapping on students' understanding of EIP and assessed initial validity and reliability of the grading rubric. Results: Students demonstrated a deeper understanding of EIP and its relationship to healthcare practice following the concept mapping activity compared to a note‐taking activity (Cohen's d = 1.79). The concept mapping rubric used to assess EIP competence demonstrated strong construct validity and content validity with moderate inter‐rater reliability. Conclusions: Employing the concept mapping technique as a teaching and learning tool proved to be effective to teach EIP principles and concepts based on student grades. An analytic rubric method was found valid and reliable for grading student concept maps underpinning EIP competency.